Análise do desempenho termoenergético de escolas públicas segundo aplicação do RTQ-C para a envoltória - Paulse, Pablo de Caldas (2016)
The search for buildings with better energy performance has been the subject of several studies, due to the energy crisis that Brazil and the world are facing and the need for a more sustainable solution for buildings. In this context, this thesis presented the analysis of the envelope (vertical walls and roof) of a school building whose purpose is to optimize its thermoenergetic performance and the achievement of higher levels of indoor thermal comfort for its users. The object of study was a standard building for classrooms of public schools in the city of Goiania–GO, whose dimensions and spatial characteristics have not been changed significantly; the analysis focusing only the building components that characterize its envelope. The thermoenergetic assessment of the proposed building was based on the Quality of Technical Regulation Methodology for Energy Efficiency of Commercial Buildings, Services and Public - RTQ-C of the Brazilian Labeling Program in Buildings (PBE Edifica), which establishes parameters for the classification of energy performance through the National Energy Conservation Label (ENCE). For this purpose, analysis were carried out of the building envelope according to the prescriptive method, based on calculations and parameters pre-set by the Regulation, and on computer simulations carried out by creating scenarios using materials and solutions recommended by the Regulation and performance of technical standards buildings (NBR 15575: 2013) and thermal performance in buildings (NBR 15220: 2005), both referenced by RTQ-C. For the simulations was used the DesignBuilder software. Simulated models were evaluated according to two criteria: the indoor air temperature and the thermal comfort of users defined by the PMV index. The results were applied to the RTQ-C methodology and demonstrate that the changes in the type of masonry and in the roof of the original model, added to the incorporation of shading elements in the openings, can provide a change in the ENCE final classification, which moves up from a medium ranking (level C) to that of maximum performance (level A), with considerable implications for the internal temperature and the percentage of hours in comfort of users, without the need for use of mechanized and high energy consuming air conditioning systems. These results provide subsidies for the development of more energy efficient public buildings, through the employment of construction systems appropriate to the site and enabling the reduction of costs associated with the maintenance of adequate thermal comfort of its users.